1990
DOI: 10.1002/cjce.5450680412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particle trajectories of small particles in flotation when the particles and bubbles are both charged

Abstract: The trajectory of a small particle moving to a bubble surface was analyzed by taking into account the effects of surface charges of the bubble and particle and the short range hydrodynamic interaction near the bubble surface, in a flotation process. The particle trajectories obtained theoretically were in good agreement with those obtained by direct observation. Even if the signs of the surface charges of the bubble and particle were the same, the particle adhered to the bubble surface when the net surface for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In Eqs. [9] and [10] above, A is the Hamaker constant. Since the van der Waals force is the net result of induced dipoledipole interactions between the molecules comprising spheres 1 and 2, the Hamaker constant depends on the composition of the two spheres and on the medium between the two spheres.…”
Section: The Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Eqs. [9] and [10] above, A is the Hamaker constant. Since the van der Waals force is the net result of induced dipoledipole interactions between the molecules comprising spheres 1 and 2, the Hamaker constant depends on the composition of the two spheres and on the medium between the two spheres.…”
Section: The Mathematical Formulationmentioning
confidence: 99%
“…Experiments by Collins and Jameson (18,19) and others (20 -22) have shown that collision efficiencies can be dramatically altered by changing the electrical properties of the bubble and particle surfaces and of the surrounding fluid. The experiments by Okada et al (10) have also shown that the relative trajectories of particles around bubbles can be strongly effected by electrostatic forces. In this paper the influence of electrostatic forces (which were neglected in (7)) and van der Waals forces will be included in a mathematical model of the interaction of a rising bubble and a solid spherical particle in microbubble flotation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For two spherical particles with zeta-potentials between À60 mV and 60 mV (Hogg et al, 1965) the electrostatic interaction force can be approximated with the following equation (Hogg et al, 1965;Okada et al, 1990a):…”
Section: Electrostatic Interactionmentioning
confidence: 99%
“…In order to calculate the interaction force between a surface and a spherical particle at close distances the diameter of one of the two spheres can again be chosen much larger than the other. This results in the following approximation (Hogg et al, 1965;Okada et al, 1990a):…”
Section: Electrostatic Interactionmentioning
confidence: 99%